5- Idéologie et développement en Guinée - Cournanel, Alain (Africa Development, 1977)
The author sets out to describe the links between economic stra tegy, class struggle and ideology in the Republic of Guinea since Inde pendence in 1958. Under the influence of such Marxist planners as Charles Bettelheim, priority was given during the first stage of econo mic strategy to growth based on national accumulation. In practice, however, only the instruments of economic autonomy (national mone tary zone, state-controlled banking and trade system) were created while existing and developing capitalist relations of production remained inchanged. This strategy was officially altered in the early sixties, before the end of the Marxist inspired Three-Year Development Plan. The second stage of economic strategy, still in force today, is characterized by growing dependence on foreign capital concentrated in big mining projects and these now determine economic planning (Seven-Year Plan 1964-1971 ; Five-Year Plan 1973-1978). The result of the new strategy has been remarkable economic stagnation since 1967. Such an economic situation leads to an intensified class struggle not only between working class organizations (trade unions) and the emerging bureaucratic bourgeoisie, but also between the different groups of the ruling class (« state » and « private » bourgeoisie). The conflicts in 1964/65 and 1969/71 resulted in a victory for a small leading group of the bureaucratic bourgeoisie over the « private » (commercial) bourgeoisie and their allies within the bureaucratic bour geoisie. The most important instrument of this group is the unity party (PDG-Parti Démocratique de Guinée). During its first phase (national democracy) the ideology of the PDG did not accept the existence of social classes in Africa and it was not until the 8th Party Congress in 1967 that Sekou Toure spoke of an emerging « lumpen-bourgeoisie ». However, in PDG terms, this social class is mainly characterized by negative conduct (corruption, etc.) and not by fundamental economic interests. As a result, scapegoats are punished while the relations of production are neither analyzed nor changed. Thus, the ideology of the PDG is revealed as an efficient social instrument within the Guinean state capitalism and its social reproduction.